2021
DOI: 10.1017/s0021932021000559
|View full text |Cite
|
Sign up to set email alerts
|

Do women with autonomy in the household experience less intimate partner violence in Malawi? Evidence from the 2015–16 Demographic and Health Survey

Abstract: In Malawi, the prevalence of intimate partner violence (IPV), or closely related violence, is estimated at 42% according to the 2015–16 Malawi Demography and Health Survey (MDHS). This study investigated the association between women’s autonomy in household decision-making participation as well as sexual autonomy and IPV among married and cohabiting women aged 15–49 years in Malawi. Secondary data were taken from the 2015–16 MDHS. Multivariate analysis was performed using a stepwise forward logistic (binary) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Studies in countries such as Ghana, Zimbabwe, and Pakistan have reported a similar association [ 13 , 14 , 36 ]. However, this association was not found in other countries such as Malawi, which described no relationship between IPV and women’s autonomy [ 37 ]. Cultural differences could explain the discrepancy in the findings between countries, and thus, the problem of IPV should be studied according to the sociocultural context of each country.…”
Section: Discussionmentioning
confidence: 95%
“…Studies in countries such as Ghana, Zimbabwe, and Pakistan have reported a similar association [ 13 , 14 , 36 ]. However, this association was not found in other countries such as Malawi, which described no relationship between IPV and women’s autonomy [ 37 ]. Cultural differences could explain the discrepancy in the findings between countries, and thus, the problem of IPV should be studied according to the sociocultural context of each country.…”
Section: Discussionmentioning
confidence: 95%
“…There is a need for interventions to be made especially for groups at risk for exposure to dating violence, and psychosocial support services to be offered to couples (30). In addition, it would be beneficial to conduct qualitative and quantitative studies that will investigate the reasons why young people tend to violence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the prevalence of physical abuse have shown that approximately 56% of women in Uganda (Karamagi et al 2006) and 47% of women in Malawi (Hindin & Muntifering, 2011) have experienced physical violence by intimate partners. This high prevalence rate of physical violence against women points to the need for targeted interventions in both countries (Forty, 2022).…”
Section: Physical Abuse In Uganda and Malawimentioning
confidence: 99%